A Systematic Literature Review (SLR) Determined the Medical Experiential Learning Development Model - Nor Shela Saleha, Nor Shela Saleha; Rosli, Mohd Shafie; Abu Bakar, Thuaibah@Suaibah; Md. Ali, Azlah (2023)
Experiential learning is essential for individual and organisational career development. The challenge and prominence of doctor experimentation were perceived as components of the request for housemanship to be recognised as a defining moment in its impact. Analysing the significant relationship between experimental learning and supervisory, communication, and knowledge applications demonstrates supervisory, communication, and knowledge implementations. Through a systematic review of the literature, this research utilises a critical analysis approach. A total of 84 journals were approached to obtain the perspectives of previous researchers on the issue of housemanship in the context of experiential learning. The study's central emphasis is on trainee doctors and medical practitioners. However, the primary focus is on medical students. Multiple philosophies have been investigated, including experiential learning, the challenges of experiential learning, and the repercussions of experiential learning. Meanwhile, knowledge intervention, supervision intervention, and communication intervention domains for experiential learning were identified. As a result of the SLR analysis, a study was created that proposed model development for experiential learning in the context of housemanship.